Prognostic significance of the 8th edition of the TNM classification for patients with extensive disease small cell lung cancer - Shirasawa M; Fukui T; Kusuhara S; Hiyoshi Y; Ishihara M; Kasajima M; Nakahara Y; Otani S; Igawa S; Yokoba M; Mitsufuji H; Kubota M; et al. (Cancer Management and Research, 2018)
Masayuki Shirasawa,1,* Tomoya Fukui,1,* Seiichiro Kusuhara,1 Yasuhiro Hiyoshi,1 Mikiko Ishihara,1 Masashi Kasajima,1 Yoshiro Nakahara,1 Sakiko Otani,1 Satoshi Igawa,1 Masanori Yokoba,2 Hisashi Mitsufuji,3 Masaru Kubota,1 Masato Katagiri,1 Jiichiro Sasaki,4 Katsuhiko Naoki1 1Department of Respiratory Medicine, Kitasato University School of Medicine, Kanagawa, Japan; 2Department of Medical Laboratory, Kitasato University School of Allied Health Sciences, Kanagawa, Japan; 3Fundamental Nursing, Kitasato University School of Nursing, Kanagawa, Japan; 4Research and Development Center for New Medical Frontiers, Kitasato University School of Medicine, Kanagawa, Japan *These authors contributed equally to this work Background: Small cell lung cancer (SCLC) is typically categorized according to disease extent as limited or extensive, and utility of the 8th TNM classification, recommended for lung cancer staging, which demonstrates a strong association with non-small-cell lung cancer (NSCLC) management, remains unclear.Methods: This retrospective study included 277 consecutive SCLC patients treated at a single institution between 2008 and 2016.Results: According to the currently used two-stage system, 186 (65.7%) of the patients were classified as having extensive disease (ED)-SCLC. Among the ED-SCLC patients, ten (5.3%), 38 (20.4%), 32 (17.2%), and 106 (57.0%) were categorized into stages M0, M1a, M1b, and M1c, respectively, according to the 8th TNM classification. There was a significant difference in overall survival based on the M descriptors: 15.8 (95% CI 9.4–22.2) months in the M1b group vs 7.3 (95% CI 5.7–8.9) months in the M1c group (P<0.001). Multivariate analysis showed that in addition to the known prognostic factors such as performance status, serum albumin, and lactate dehydrogenase, M descriptor was a prognostic factor (HR 1.95, 95% CI 1.38–2.77; P<0.001).Conclusion: The 8th TNM classification has a prognostic value in SCLC. Similarly to NSCLC, treatment approaches should be considered on the basis of the 8th TNM classification, especially stage IVA separate from stage IVB in ED-SCLC patients. Keywords: small cell lung cancer, extensive disease, TNM stage, prognosis